Occurrence of Enterobacteriaceae in medicinal plants sold in local markets of Savar, Dhaka - Doula, SM Rokon Ud; Afrin, Nazia; Shilpi, Rasheda Yasmin (Jahangirnagar University Journal of Biological Sciences, 2022)
Medicinal plants can be contaminated with a large diversity of potentially pathogenic bacteria. Ten medicinal plant samples Plantago psyllium, Terminalia bellirica, Terminalia chebula, Phyllanthus emblica, Ocimum basilicum, Glycyrrhiza glabra, Withania somnifera, Andrographis panicula, Bombax ceiba were collected from Amin Bazar and Savar of Savar area to study the presence and abundance of Enterobacteriaceae family bacteria in the herbal plant samples. A total of fifty five (55) bacterial isolates have been isolated from different medicinal plant samples using spread plate method on nutrient Agar media. Culture of bacterial isolate on a number of selective and differential media and biochemical tests (Catalase activity, hemolytic property, fermentation test, Starch hydrolysis, VP test, MR test, MIU test, Indole and casein test etc.) revealed the presence of different Enterobacteriaceae family bacteria in the plant samples. Out of 55 isolates 6 isolates were Salmonella sp. (11%), 2 isolates were Klebsiella sp. (3.63%) and 2 isolates were Enterobacter sp. (3.63%). Antibiotic sensitivity test of bacterial isolates showed that all the identified Enterobacteriaceae family bacteria were sensitive to Kanamycin but resistant to Amoxycilin, Aztreonam and Penicillin-G. Therefore, this study highlighted the necessity for constant quality assessment of herbal medicines to facilitate and ensure safe production and supply of medicinal products suitable for human consumption. Jahangirnagar University J. Biol. Sci. 10(1 & 2): 1-8, 2021 (June & December)